Faktor-Faktor Yang Berhubungan Dengan Kejadian Infeksi Saluran Pernapasan Akutpada Anak Balita di Wilayah Kerja UPTD Puskesmas Tanjung Baru Kec. Baturaja Timur Kab. OKU Tahun 2021 - Riza Ariani; Dianita Ekawati (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Ispa incident in toddlers in UPTD Puskesmas Tanjung Baru ranked number one andbecame a priority issue in puskesmas. To find out the factors related to the Incidence of ISPA in toddlers in the working area of UPTD Puskesmas Tanjung Baru Kecamatan Baturaja Timur Kabupaten Ogan Komering Ulu Year 2021. Cross Sectional research design, the population in the study is a toddler in the working area of UPTD Puskesmas Tanjung Baru Kecamatan Baturaja Timur Kabupaten Ogan Komering Uluin 2021. Sampling method with purposive sampling technique. The subject of this study was determined by Purposive sampling, namely toddlers in the working area of UPTD Puskesmas Tanjung Baru East Baturaja District Ogan Komering Uluin 2021 amounted to 115 respondents. Data collection using questionnaires. The results of the statistical test analysis of respondents using the Chi-Square test showed there is a relationship (p< 0.05) for ventilation, occupancy of nutritional status and smoking habits. The results of the study showed that there is a relationship between ventilation and ispa incidence in toddlers (p value = 0.03), there is a relationship between occupancy density and ISPA incidence in toddlers (p value = 0.00), there is a relationship between smoking and ISPA incidence in toddlers (p value = 0.00), then the Puskesmas should provide information related to ISPA disease by using electronic media , so that the information reaches the public